The Impact of Dual-Experience Flexible Work Arrangements on Employee Performance: The Moderating Role of E-Work Self-Efficacy - Bagus Adi Luthfi; Pantius Drahen Soeling; Chandra Wijaya (Journal Research of Social Science, Economics, and Management, 2025)
The impact of flexible work arrangements (FWA) on employee performance remains inconclusive due to the tendency of prior research to analyze the phenomenon from a single perspective, either that of the employee or the organization. This study aims to address this gap by examining the influence of two forms of FWA—flexibility as a contribution and flexibility as an inducement—on employee performance, while also investigating the moderating role of e-work self-efficacy. Guided by social exchange theory and the Job Demands-Resources (JD-R) model, an online survey was conducted using a cross-sectional design, collecting 545 valid responses from employees in the ICT-based industry. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that flexibility as a contribution negatively impacts employee performance, whereas flexibility as an inducement has a positive effect. The moderation analysis further shows that e-work self-efficacy significantly moderates the relationship between flexibility as a contribution and both task and contextual performance but not adaptive performance. Similarly, e-work self-efficacy significantly moderates the relationship between flexibility as an inducement and task performance but not contextual or adaptive performance. This study concludes that the effects of FWA on employee performance are nuanced and depend on the form of flexibility offered and the level of employees’ e-work self-efficacy. These findings provide actionable insights for organizations to optimize FWA policies to enhance employee performance.